The Learning Curve of Gastric Intestinal Metaplasia Interpretation on the Images Obtained by Probe-Based Confocal Laser Endomicroscopy - Pittayanon, Rapat (Hindawi Publishing Corporation, 2012)
Background. Reading the results of gastric intestinal metaplasia (GIM) with probe-based confocal laser endomicroscopy (pCLE) by the expert was excellent. There is a lack of study on the learning curve for GIM interpretation. Therefore, we conducted a study to explore the learning curve in the beginners. Material and Method. Five GI fellows who had no experience in GIM interpretation had been trained with a set of 10 pCLE video clips of GIM and non-GIM until they were able to interpret correctly. Then they were asked to interpret another 80 video clips of GIM and non-GIM. The sensitivity, specificity, accuracy, PPV, NPV, and interobserver agreement on each session were analyzed. Results. Within 2 sessions, all beginners can achieve 80% accuracy with substantial to almost perfect level of interobserver agreement. The sensitivities and specificities among all interpreters were not different statistically. Four out of five interpreters can maintain their high quality of reading skill. Conclusion. After a short session of training on GIM interpretation of pCLE images, the beginners can achieve a high level of reading accuracy with at least substantial level of interobserver agreement. Once they achieve the high reading accuracy, almost all can maintain their high quality of reading skill.